Forecasting circular economy indicators: A Machine Learning study of European Union member states - Niamh McMahon; Colin Fitzpatrick; Cornelis P. Baldé; Sara Bottausci; Eoin M. Grua (Journal of Cleaner Production, 2026)

A statistical assessment of the EU packaging waste directive (2004 Amendment) on plastic packaging recycling in the EU - Paul Mullane; Sara Bottausci; Cornelis Peter Baldé; Colin Fitzpatrick; Eoin Martino Grua (Resources, Conservation and Recycling, 2026)

Product lifetimes and industrial ecology - Jessika Luth Richter; Tamar Makov; Keshav Parajuly; Conny Bakker; Colin Fitzpatrick (Journal of Industrial Ecology, 2024)

A tasty solution to packaging waste? Life cycle assessment of edible coffee cups - Keteki Anand; Andrés Martinez Arce; George Bishop; David Styles; Colin Fitzpatrick (Resources, Conservation and Recycling, 2024)

Product repair in a circular economy: Exploring public repair behavior from a systems perspective - Keshav Parajuly; James Green; Jessika Richter; Michael Johnson; Jana Rückschloss; Jef Peeters; Ruediger Kuehr; Colin Fitzpatrick (Journal of Industrial Ecology, 2024)
Repair practices are driven not only by consumers’ internal motivation, but also by external infrastructural, social including cultural, financial, and political factors. We explore these factors with the goal of understanding the public repair of electrical and electronic products (e‐products) from a systems perspective to help devise appropriate change interventions. We document (a) behavioral aspects, (b) techno‐economic factors, and (c) intervention strategies aimed at promoting repair practices. To gauge this, a survey was administered among 922 volunteers across 14 countries with experience in repairing e‐products at public repair events. Findings suggest that while behavioral constructs including personal values, beliefs, and attitudes toward product repair are the main proximal drivers of intention to repair, the ability to repair plays an important role. Further, these individual factors are influenced by the techno‐economic settings such as access to repair services, economic benefits, and the ease of product repair stands out as the key enablers for product lifetime extension. As per intervention strategies, the results highlight economic incentives, regulatory requirements, and public awareness as the key drivers. However, influencing repair behavior directly may not always be the most effective strategy. New initiatives to improve involvement should focus on more repairable products, exploiting the innovative potentials of commercial as well as non‐profit repair initiatives, education, and supporting the development of skills among volunteer repairers.

Characterizing IT asset disposition flows for the circular economy: A case study on export for reuse from Ireland - Kathleen McMahon; Chidinma Uchendu; Colin Fitzpatrick (Journal of Industrial Ecology, 2023)
Understanding flows of resource‐rich electrical and electronic equipment throughout its life cycle is increasingly important in the development of global circular economies, reflected by heavy legislative focuses on waste prevention and resource use efficiency. This research facilitates broader material flow analysis by characterizing flows of professional IT equipment within the Republic of Ireland, emphasizing the flow of legal exports for the purposes of refurbishment and reuse. The analysis of transboundary movement of non‐waste used equipment contributes to a less often measured, but influential, facet of material flows. Eight key exporters of used equipment, comprising original equipment manufacturers, information technology asset disposition companies, and waste treatment facilities, were interviewed to characterize the sector, map the flow of materials, and identify gaps in existing reporting. Interviewed organizations declared exports of used equipment by category using a voluntary declaration form. Two key flows were identified representing currently unreported and unmeasured flows of non‐waste professional equipment. A total of 441,261 units of equipment were declared to be exported for reuse from the Republic of Ireland through these previously unmeasured flows in 2019. Product keys developed by United Nations University were used to estimate the weight of total units exported as approximately 576 metric tons, amounting to an additional approximately 9% of the weight of IT equipment collected in the Republic of Ireland in 2018, or 0.1 kg per inhabitant. These quantifications of IT equipment exported for reuse will be a key component of future material flow analyses in the development of a circular economy.

Uncaptured mercury lost to the environment from waste electrical and electronic equipment (WEEE) in scrap metal and municipal wastes - Yvonne Ryan-Fogarty; Cornelis Peter Baldé; Michelle Wagner; Colin Fitzpatrick (Resources, Conservation and Recycling, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Quantifying WEEE arising in scrap metal collections: Method development and application in Ireland - Yvonne Ryan‐Fogarty; Damian Coughlan; Colin Fitzpatrick (Journal of Industrial Ecology, 2021)

Evaluating the sustainability potential of a white goods refurbishment program - Maurice W. O’Connell; Stewart W. Hickey; Colin Fitzpatrick (Sustainability Science, 2013)

Feasibility of Using Radio Frequency Identification to Facilitate Individual Producer Responsibility for Waste Electrical and Electronic Equipment - Maurice O'Connell; Stewart Hickey; Maria Besiou; Colin Fitzpatrick; Luk N. Van Wassenhove (Journal of Industrial Ecology, 2013)
Summary Regulatory measures that hold producers accountable for their products at end of life are increasingly common. Some of these measures aim at generating incentives for producers to design products that will be easier and cheaper to recover at the postconsumer stage. However, the allocation of recovery costs to individual producers, which can facilitate realization of the goals of these policies, is hindered by the practical barrier of identification and/or sorting of the products in the waste stream. Technologies such as radio frequency identification (RFID) can be used for brand or model recognition in order to overcome this obstacle. This article assesses the read rate of RFID technology (i.e., the number of successful retrievals of RFID tag data [“reads”] in a given sample of tagged products) and the potential role of RFID tags in the management of waste electrical and electronic equipment (WEEE) at current levels of technical development. We present the results of RFID trials conducted at a civic amenity site in the city of Limerick, Ireland. The experiment was performed for fixed distances up to 2 meters on different material substrates. In the case of white goods (i.e., large household appliances), a 100% read rate was achieved using an RFID handheld reader. High read rates were also achieved for mixed WEEE. For a handheld scan of a steel cage containing mixed WEEE, read rates varied from 50% to 73% depending on the ultrahigh frequency (UHF) metal mount tag employed and the relative positioning of the tags within the cage. These results confirm that from a technical standpoint, RFID can achieve much greater brand or model identification than has been considered feasible up to now, and thus has a role to play in creating a system that allocates recovery costs to individual producers.

Clinical and molecular genetic features of ARC syndrome - Paul Gissen; Louise Tee; Colin A. Johnson; Emmanuelle Genin; Almuth Caliebe; David Chitayat; Carol Clericuzio; Jonas Denecke; Maja Di Rocco; Björn Fischler; David FitzPatrick; Angeles García-Cazorla; et al. (Human Genetics, 2006)